(untitled) (International Journal of Physiotherapy, 2016)
Background: Scrotal discomfort can contribute to unusual impact on body scheme and result in behavioral alterations, as well as changes in sexual function such as delay of sexual ability that may affect both man and his companion. There are many physiotherapy modalities to reduce the intratesticular pain such as pelvic floor muscle training, hydrotherapy, ultrasound and electrotherapy. Interferential current therapy is a noninvasive therapy used to reduce acute and chronic, post-operative and post-trauma acute pain. It provides a safe and effective alternative to pharmacological approaches to pain control. The purpose of the current study was to investigate the efficacy of interferential current in alleviating testicular pain. Methods: Randomized clinical study conducted on 50 participants. They divided into two equal groups: Group A received interferential current with two electrodes placed over the upper medial aspects of thighs and the other two electrodes were positioned over the suprapubic area. While group B received placebo interferential current. The treatment protocol was applied 3 times/ week for six successive weeks, in a total of 18 sessions. Patients were evaluated before and after the six weeks of the treatment by visual analogue scale and pain intensity while pain relief scale was measured after the treatment. Results: Group A showed a significant pain improvement in both inter and intra group comparison in all measured parameters (visual analogue scale and pain intensity while pain relief scale) (p <0.05). Conclusion: The findings show that interferential current is an effective modality and can be recommended for the treatment of testicular pain.